Investigating Project Cost Management For High-Rise Residential Buildings - Ling, Chee Soon (2021)
Malaysia was a developing country whose economy was still dominated by construction, especially high-rise residential buildings. But construction was consistently rated locally as one of the country's most dangerous industrial activities, which would affect the country's gross domestic product (GDP). For the researched aimed was the purpose of this studied was to understand and analyze the costed overruns that often occurrence in the construction industry of high-rise residential buildings in Klang Valley. In ordered to ensure that the construction costed management of the high-rise construction project was within the budget range, cost control in the construction project was an important factor. The construction of the project in the construction of over-expenditure phenomenon in the field of common occur. The length of the project development phase from preliminary planning to construction appears to have been a major factor in the extent of cost overruns. The longer it took and the bigger the project, the easier it was to create cost overruns. The study would be able to identify cost overruns that affect the total building cost. The cost overrun of construction projects was due to a variety of reasons, and many researchers had conducted a variety of studies to determine the factors that caused this problem. In recent years, the concept of construction cost over time have had attracted extensive attention. Many studies tried to identify and analyze the factors of cost overrun, the influence on the construction industry and found out the most important solution to overcome the cost overrun. The researched methodology method was used quantitative method in this researched. The data analysis would use SPSS software for further analysis of the data collected from the respondents, techniques used in data analysis included Cronbach’s alpha, Mean ranking, Kruskal-Wallis test, One-sample t-test, and Spearman`s correlation test. The findings of this surveyed review that the main factor causing cost overruns in the construction industry was poor financial management, and that the most important solution to overcome cost overruns would be effective site management and supervision. Cost management in the construction industry would effectively result in lost profits for contractors, sub-contractor, consultants and developers.